Caracterização do eletrocardiograma basal de ratos infectados pelo T. cruzi - Bestetti, Reinaldo B. (1987)
A total of 125 rats were infected with the Colômbia strain of T. cruzi (2000 parasites/g) shortly after weaning. Of these, 58 survived the acute phase and were used in the present experiment. Twenty eight similar but not infected rats served as controls. All rats were submitted to the resting ECG When they were 6 months old. Classic and 3 precordial leads were employed in order to record the ECG as completely as possible. Electrocardiographic changes similar to those found in human chronic Chagas' heart disease and not previously described in this model were found in 44% of the T. cruzi-infected rats: left axis deviation (22%), right axis deviation (7%), lengthened and bizarre QRS complex (14%) and abnormal J point elevation (3%). On the basis of these results, we believe that the resting ECG constitutes a valuable tool for studying experimental chronic Chagas' heart disease in rats.